2000
DOI: 10.1023/a:1005140631988
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Examination of the Transition into Senior High School for Adolescents from Urban, Low‐Income Status, and Predominantly Minority Backgrounds

Abstract: The current 6-year study investigates the impact of the elementary (K-8)-to-high school (9-12) transition on the school completion outcomes of 107 adolescents from urban, minority, low-income status backgrounds. Descriptive findings provide a longitudinal profile of students' enrollment status throughout high school. Students who had graduated or were Active in the school system at the end of the study evidenced more marked change in perceptions of social support following the transition to the ninth grade com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 35 publications
8
69
0
5
Order By: Relevance
“…Alspaugh's (1998), Feiner et al 's (1981 and Crockett et al 's (1989) studies (outlined previously) all reported declines in students' MMA T scores, GP A, and end of year grades for students making middle and high school transitions. These findings have been supported by other researchers (Alspaugh, 1998;Barone et al, 1991;Crockett et al, 1989;Feiner et al, 1981;Isakson & Jarvis, 1999;Ratelle et al, 2004;Reyes et al, 2000). Barone et al (1991) investigated the middle to high school transition for 82 students.…”
Section: The Effect Of School Transitions On Student Outcomessupporting
confidence: 67%
See 3 more Smart Citations
“…Alspaugh's (1998), Feiner et al 's (1981 and Crockett et al 's (1989) studies (outlined previously) all reported declines in students' MMA T scores, GP A, and end of year grades for students making middle and high school transitions. These findings have been supported by other researchers (Alspaugh, 1998;Barone et al, 1991;Crockett et al, 1989;Feiner et al, 1981;Isakson & Jarvis, 1999;Ratelle et al, 2004;Reyes et al, 2000). Barone et al (1991) investigated the middle to high school transition for 82 students.…”
Section: The Effect Of School Transitions On Student Outcomessupporting
confidence: 67%
“…In conclusion the review will provide a summary of the research limitations and suggestions for future research. It appears that transition research has focused primarily on American, metropolitan schools, and students undergoing the elementary to middle school transition at approximately 11 years old (Alspaugh, 1998;Barone et al, 1991;Blyth, Simmons, & Bush, 1978;Blyth et al, 1983;Cotterell, 1992;Crockett et al, 1989;Feiner et al, 1981;Hirsch & DuBois, 1992;Hirsch & Rapkin, 1987;Isakson & Jarvis, 1999;Reyes et al, 2000;Schiller, 1999). Furthermore, quantitative methodologies have predominantly been utilised (Alspaugh, 1998;Barone et al, 1991;Blyth et al, 1978;Blyth et al, 1983;Cotterell, 1992;Crockett et al, 1989;Feiner et al, 1981;Hirsch & DuBois, 1992;Hirsch & Rapkin, 1987;Isakson & Jarvis, 1999;Reyes et al, 2000;Schiller, 1999), providing useful information on the effects of school transitions but not on the qualitative experience from the students' perspectives (Brown & Armstrong, 1982;Johnstone, 2001Johnstone, , 2002Rowland, 2002;Yates, 1999).…”
Section: Adolescents and School Transitions: A Review Of The Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Gutman and Midgley 2000;Jindal-Snape and Foggie 2008;Newman et al 2000;Reyes et al 2000), less research has been conducted specifically on the perceptions of pupils in the final year of primary school (known as 'group 8' in the Dutch school system) on the preparatory process for the transition to secondary school (Akos and Galassi 2004;Ashton 2008;Tobbell and O'Donnell 2013), and especially on the preparatory process of pupils with a migrant background (Benner and Graham 2009;McGee et al 2003). The present small-scale qualitative study examines how Dutch pupils with a migrant background perceive and experience this preparatory process, and how they can be encouraged and supported in preparing for the transition to secondary education in the Dutch system (i.e.…”
Section: Introductionmentioning
confidence: 99%